2017
DOI: 10.3390/biomedicines5020013
|View full text |Cite
|
Sign up to set email alerts
|

HLA-C KIR-Ligands Determine the Impact of Anti-Thymocyte Globulin (ATG) on Graft versus Host and Graft versus Leukemia Effects Following Hematopoietic Stem Cell Transplantation

Abstract: Rabbit anti-thymocyte globulins (ATGs) are widely used for the prevention of acute and chronic graft versus host disease (aGVHD, cGVHD) following allogeneic hematopoietic stem cell transplantation (HSCT). However, most prospective and retrospective studies did not reveal an overall survival (OS) benefit associated with ATG. Homozygosity for human leukocyte antigen (HLA)-C group 1 killer-cell immunoglobulin-like receptor ligands (KIR-L), i.e. C1/1 KIR-L status, was recently shown to be a risk factor for severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…However, T cell-depleted HLA-C1/C2 recipients relapsed much more frequently even if they had received a myeloablative regimen, indicating that T cell depletion affected the GVL effect, and that other KIRs on NK cells might not trigger sufficient GVL reactivity. These results agree with a report from Austrian European Society for Blood and Marrow Transplantation centers, in which HLA-C1/C1 recipients experienced the greatest benefits of ATG for survival compared with HLA-C1/C2 or HLA-C2/C2 recipients [38]; however, survival and relapse of their HLA-C1/C2 recipients using ATG were not as negative as those in our present series.…”
Section: Discussionsupporting
confidence: 92%
“…However, T cell-depleted HLA-C1/C2 recipients relapsed much more frequently even if they had received a myeloablative regimen, indicating that T cell depletion affected the GVL effect, and that other KIRs on NK cells might not trigger sufficient GVL reactivity. These results agree with a report from Austrian European Society for Blood and Marrow Transplantation centers, in which HLA-C1/C1 recipients experienced the greatest benefits of ATG for survival compared with HLA-C1/C2 or HLA-C2/C2 recipients [38]; however, survival and relapse of their HLA-C1/C2 recipients using ATG were not as negative as those in our present series.…”
Section: Discussionsupporting
confidence: 92%
“…Multivariate analysis using a Cox proportional hazard model from the findings of Yabe and Clausen suggested that ATG preadministration was a critical factor in grade III-IV aGVHD under consideration of the HLA-C KIR-L status (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, using Cox proportional hazard modeling, we showed that grade of GVHD after the time of transplantation and ATG conditioning regimen were prognostic factors affecting transplant survival. Multivariate analysis using a Cox proportional hazard model from the findings of Yabe and Clausen suggested that ATG preadministration was a critical factor in grade III-IV aGVHD under consideration of the HLA-C KIR-L status (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Clausen et al observed an opposite effect of missing KIR ligands in patients transplanted with bone marrow when compared to peripheral blood stem cells as graft source, in recipients homozygous for HLA-C group 2 ligands for inhibitory killer Ig-like receptors [ 44 ]. Recently, the same authors suggested that the use of anti-thymocyte globulin (ATG) may provide a survival benefit in recipients with at least one C1 group KIR-L, by reducing transplant-related mortality (TRM) without significantly increasing the relapse risk [ 45 ]. Given the central role of NK cell alloreactivity in preventing leukemia relapse, in the setting of haplo-HSCT it is crucial to determine in different potential donors if alloreactive NK cells are present and the size of such alloreactive populations.…”
Section: Natural Killer (Nk) Cells and Kir/kir Ligand Polymorphismmentioning
confidence: 99%